Thymineless Death in Bacillus subtilis: Correlation Between Cell Lysis and Deoxyribonucleic Acid Breakdown - Ephrati-Elizur, E. (1974)
Bacillus subtilis carrying an inducible defective phage is several times more sensitive to thymineless death than a mutagenized derivative that behaves as a nonlysogen. When the integrity of the deoxyribonucleic acid (DNA) of both strains was examined during thymine starvation by transformation experiments, sedimentation studies, and measurements of acid-soluble DNA degradation products, it was shown that extensive DNA breakdown occurred only in the lysogenic strain. During thymine starvation of this strain, there is a progressive proclivity to lysis, followed by leakage of DNA and DNA degradation products. Such leakage was not observed in the nonlysogen. A correlation between proclivity to lysis and extensive DNA degradation is indicated.